Channels for Narrowing the US Current Account Deficit and Implications for Other Economies - Brook, Anne-Marie (OECD Economics Department Working Papers, 2004)
In this paper the OECD's interlink model is used to explore several possible channels through which a narrowing of the US current account deficit could occur. The shocks considered include dollar depreciation, fiscal consolidation, and an improvement in the non-price competitiveness of US producers. A key conclusion is that shocks would have to be very large in order to materially reduce the US external deficit. In part, this is because second-round effects, including domestic policy responses, tend to offset the shocks' initial impact. In addition, it is clear that each of the channels for narrowing the deficit involves risks to growth in the rest of the world, particularly in Japan where the authorities have limited room to use monetary or fiscal policy to offset any contractionary pressures. The exchange rate simulations highlight the fact that more exchange rate flexibility in Asia would spread the burden of adjustment more evenly across US trading partners. Attention is also ...